Minimally Invasive Carpal Tunnel Release (CTR) Using the Wongsiri Technique with MiniSURE - Sunton Wongsiri; Wongthawat Liawrungrueang (Advances in Orthopedics)
Introduction. The standard open technique for carpal tunnel surgery has wound problems and complications significantly more than minimally invasive surgery using the Wongsiri technique with MiniSURE Kit® (Surgical Innovation Healthcare Co., Ltd, Bangkok, Thailand) and in particular, the open technique surgery requires a longer time for return to work. CTR surgery with endoscopic devices improves the results with fewer wound problems when compared with the commonly used open technique; however, nerve complications and injury are more prevalent with endoscopic surgery than with the open technique. The Wongsiri technique produces good results with new medical devices such as the MiniSURE View, for improved vision and line-of-sight, and the MiniSURE Cut for improved and complete cutting via the supraretinacular technique that may reduce the nerve problems associated with endoscopic tooling in the carpal tunnel. Purpose. To evaluate the results of the operation and postoperative outcomes of the Wongsiri technique with a MiniSURE Kit®. Methods. 20 patients underwent carpal tunnel release using the Wongsiri technique and a MiniSURE Kit® with a five-step surgery: MIS starts when the surgeon makes a 1.5–1.8 cm incision, creates a working space, inserts the visual tube of MiniSURE View, inserts the freer, and then cuts the transverse carpal ligament by using the MiniSURE Cut. Results. All 20 successes of the Wongsiri technique and MiniSURE Kit® surgery occurred within 6.8 minutes operative time and a 12 mm wound size. A single outlier, in one case (6.7%), the patient experienced pillar pain which abated within one month. Patients can return to work in 7.3 days. Conclusions. The Wongsiri technique with the MiniSURE Kit® demonstrated good outcomes similar to the endoscope. By contrast with the endoscopic surgery, the Wongsiri technique with the MiniSURE Kit® reduced preop, operating, and postop time, many resources, and significant costs and resulted in no nerve problems or complications.